(untitled) (Ciudades, 2017)
The article addresses the problem of financing of the integral regeneration of neighborhoods. After the analysis of already tested models of management and financing, guidelines for a new model based on cooperativism are proposed. The economic potential of an active and unitary collective action requires a social economy model based on the provision of services as a basis for habitability and maintenance as an objective to reduce cycles of obsolescence. This articulates a long-term mechanism that transcends the single action of rehabilitation and ensures a progressive adaptation to new standards of habitability.